Proposta de reestruturação do produto medição individualizada em uma empresa de saneamento básico por meio de framework de arquitetura corporativa - Romero, Marcio (2013)
The population density in big centers such as the Metropolitan Area of São Paulo (MASP) leads to the vertical buildings and the formation of condominiums where water consumption in these buildings is not individualized thereby impedes the actions of rational use of water, once that every resident do not knows its consumption. To meet this demand the State of São Paulo Basic Sanitation Company - Sabesp, the company that was adopted in this study, since 2008 structured ProAcqua, a program for individualization of water consumption with a focus on quality, safety and reliability of measurement and began offering its customers the product Individual Metering. After four years of maturation, this product highlighted problems in commercial and operational processes and Infrastructure Technology (IT) that s involving the product Individual Metering. A review of the business strategy was performed and a survey research was applied in areas that interface with the product to confirm the problems identified and the main points of attention when implementing changes arising from the change in strategy. Was identified the need to ensure that changes in systems and processes that involve the product are implemented in a structured manner by mapping process. The objective of this work was to propose a restructuring of the Individual Metering product in a sanitation company through Enterprise Architecture framework. The Enterprise Architecture framework was chosen because allows alignment between strategy and execution, and also analyze the business process, information system and technology infrastructure. The results obtained using the Enterprise Architecture framework contributed positively to the implementation of changes in the process and system involving the product Individual Metering and it was performed in a structured manner through a global overview of all product interfaces and points of attention.